Bias Detection and Mitigation within Decision Support System: A Comprehensive Survey - Prakhar, Jyoti; Haider , Md. Tanwir Uddin (International Journal of Intelligent Systems and Applications in Engineering, 2023)
In decision support system biases plays a vital role to lead unfair and discriminatory outcomes within the system, which can have serious consequences for people and society as a whole. While significant work has been done in classical machine learning and deep learning to address these difficulties, still there is a need for extensive surveys that evaluate various real-world applications and causes of bias in decision support systems. In this paper, we present a comprehensive survey that explores the biases, detection of biases, mitigation of biases, and fairness metrics to measure the degree of fairness in decision support systems. Further, we also identified several challenges related to biases such as minimizing biases when working with inadequate datasets, ensuring proper representation of protected attributes, developing efficient and direct methods for bias detection, identifying effective approaches for mitigating biases at various stages of the model, developing strategies to effectively mitigate multiple biases in the system to build a fair prediction model and at last, exploring and refining fairness metrics to achieve more fair results. We have also provided the research questions based on these challenges with the solutions and interesting future research avenues that might help to alleviate the problem of bias in decision support systems. We hope that this poll will motivate scholars to confront these issues and help the creation of more equitable systems.